Pengaruh Manajemen Konflik, Organizational Learning, dan Komunikasi Terhadap Kinerja Karyawan di CV. XYZ Surabaya - Cahyo Rachmat Dani; Tan Evan Tandiyono (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Human Resources (HR) are an essential asset in an organization or company, as they encompass individuals with the skills, knowledge, and competencies needed to achieve organizational goals. Conflict management, organizational learning, and effective communication are the main pillars of HR management. Conflict management plays a role in transforming potential friction into opportunities for creative solutions, maintaining harmony, and improving team productivity. Organizational learning enables individuals and organizations to grow, adapt, and face new challenges with continuously evolving knowledge. Meanwhile, effective communication acts as a bridge that connects vision, mission, and actions, ensuring all elements of the organization move in alignment toward shared goals. CV. XYZ Surabaya is a company engaged in the supply and distribution of electrical equipment. Finding the right human resources for this organization is not an easy task. One of the company’s primary objectives is to improve employee performance, as improved employee performance is directly proportional to enhanced organizational performance. Based on the research findings, the t-test (partial) and f-test (simultaneous) analysis revealed that the variables of conflict management, organizational learning, and communication have a significant impact, both partially and simultaneously, on employee performance at CV. XYZ Surabaya.